The microsurgical anatomy of the glossopharyngeal nerve with respect to the jugular foramen lesions. - Ozveren, Mehmet Faik; Türe, Ugur (My University, 2004)
Removal of lesions involving the jugular foramen region requires detailed knowledge of the anatomy and anatomical landmarks of the related area, especially the lower cranial nerves. The glossopharyngeal nerve courses along the uppermost part of the jugular foramen and is well hidden in the deep layers of the neck, making this nerve is the most difficult one to identify during surgery. It may be involved in various pathological entities along its course. The glossopharyngeal nerve can also be compromised iatrogenically during the surgical treatment of such lesions. The authors define landmarks that can help identify this nerve during surgery and discuss the types of lesions that may involve each portion of the glossopharyngeal nerve.
Keywords: Atlas; Cerebellopontine Angle; Cranial Nerve Neoplasms; Endarterectomy, Carotid; Glomus Jugulare Tumor; Glossopharyngeal Nerve; Glossopharyngeal Nerve Diseases; Humans; Intraoperative Complications; Microsurgery; Neurilemmoma; Skull Base; MLCS; MLOWN; atlas; carotid endarterectomy; chemodectoma; cranial nerve tumor; glossopharyngeal nerve; glossopharyngeal nerve disease; histology; human; injury; methodology; microsurgery; neurilemoma; pathology; peroperative complication; pons angle; review; skull base